PENGARUH KESESUAIAN STRATEGI INOVASI DENGAN SISTEM KONTROL TERHADAP KINERJA KEUANGAN - Sri Hartono (Media Riset Akuntansi, Auditing & Informasi, 2005)
The objective of this study is testing of effect between product innovation strategy, process novation with operational control system to companies financial performance used Internal nsistencyAppmach.he collecting data by questionnaire via direct mail to 475 manufacturing companies director from ind of industries in Indonesia. The return of questionnaire are 63. The result of study shows here is an effect between product innovation strategy and process innovation strategy with •ntrol system to financial performance.Key words: Internal Consistency, Inovasi Produk, lnovasi Proses, Sistem Kontrol perasional Kinerja Kuangan